2020
DOI: 10.1155/2020/3505209
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Strength Training Combined with Vitamin C and E Supplementation on Skeletal Muscle Mass and Strength: A Systematic Review and Meta-Analysis

Abstract: Intense muscle contractile activity can result in reactive oxygen species production in humans. Thus, supplementation of antioxidant vitamins has been used to prevent oxidative stress, enhance performance, and improve muscle mass. In this sense, randomized controlled studies on the effect of vitamin C and E supplementation combined with strength training (ST) on skeletal muscle mass and strength have been conducted. As these studies have come to ambiguous findings, a better understanding of this topic has yet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…The studies revealed that vitamin-E supplementation in athlete improved the muscle performance and protects the cell membrane from damage through oxidative stress. This study augment that vitamin E would strengthen the skeletal muscle of the older people [39].…”
Section: Adultssupporting
confidence: 66%
“…The studies revealed that vitamin-E supplementation in athlete improved the muscle performance and protects the cell membrane from damage through oxidative stress. This study augment that vitamin E would strengthen the skeletal muscle of the older people [39].…”
Section: Adultssupporting
confidence: 66%
“…When subjects took antioxidant vitamin supplements over a chronic period and were then tested in an acute exercise session, no differences between SUP and placebo groups were found in different performance indicators: isometric torque or concentric torque [34]; maximal isometric strength in squat and bench press [33]; maximal voluntary contraction (MVA), eccentric hamstring torque and concentric quadriceps power [31]; vertical jump, agility, sprint time or fatigue index [25]; and aerobic work capacity [36]. Interestingly, a recently published systematic review and meta-analysis by Dutra et al [52] concludes that VitC and VitE SUP has no effect on muscle force production in chronic strength training and could even attenuate specific adaptions such as hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Medicinal plants are a source of important therapeutic for alleviating human ailments and the medicinal plants have bioactive compounds, which are used for curing various human disease and also play an essential role key in chronic disease to especially on spinal muscular atrophy cell system pathway [33]. The natural antioxidant as a reduces the free radical of spinal muscular atrophy, stimulates the growth of normal cells, to protects the cell against the premature and abnormal aging condition of spinal muscular atrophy, helps fight the age-related molecular degeneration of spinal muscular atrophy and the last to supports the body immune system [34,35].…”
Section: Total Antioxidant Of Abelmoschus Manihot (L) Medikmentioning
confidence: 99%